2023
DOI: 10.3389/fpubh.2023.1108336
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the link between domain satisfaction and life satisfaction during the COVID-19 pandemic: Job-related moderators in triadic analysis in dual-earner parents with adolescent children

Abstract: IntroductionResearch has evaluated the impact of COVID-19 pandemic and lockdowns on individuals' life satisfaction, but wellbeing interrelations between family members in this context have been less explored. This study examined the spillover and crossover effects of one parent's job satisfaction (JS), satisfaction with family life (SWFaL) and satisfaction with food-related life (SWFoL) on their own, their partner's, and their adolescent children's life satisfaction (LS), and the influence of adolescents' SWFa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 94 publications
0
1
0
Order By: Relevance
“…Contrary to expectations [17,50], the resource loss by one parent facing high family demands did not cross over to the other parent's job satisfaction (H4 not supported). This result may be explained considering that when actor effects are weak, as in the present study, it is likely that partner effects do not exist [14], as was previously reported in dyadic studies with dual-earner couples [e.g., [17,18]]. However, our findings are consistent with results reported by Yucel and Latshaw [36], which may be related to the fact that partner effects may be indirect effects mediated by other variables [14].…”
Section: Partner Effectssupporting
confidence: 92%
See 3 more Smart Citations
“…Contrary to expectations [17,50], the resource loss by one parent facing high family demands did not cross over to the other parent's job satisfaction (H4 not supported). This result may be explained considering that when actor effects are weak, as in the present study, it is likely that partner effects do not exist [14], as was previously reported in dyadic studies with dual-earner couples [e.g., [17,18]]. However, our findings are consistent with results reported by Yucel and Latshaw [36], which may be related to the fact that partner effects may be indirect effects mediated by other variables [14].…”
Section: Partner Effectssupporting
confidence: 92%
“…Respondents indicated their degree of agreement with each statement using a five-point Likert scale (1: completely disagree; 5: completely agree). The Spanish version of the OJSS scale was used, which has been validated and has shown good internal consistency in studies with couples in Chile [16,18]. OJSS scores were obtained by totaling the scores from the six items, with higher scores representing higher job satisfaction (score range 6-30).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parental employment and family structure were measured in 2021 and could have changed between 2020 and 2021. Furthermore, some other factors related to parents were not measured in this study and may have had a differential impact on the life satisfaction of adolescents since the beginning of the pandemic (e.g., domestic violence ( 38 ), life satisfaction of parents ( 39 )). Other confounding factors could explain the differences in the fluctuation of life satisfaction between girls and boys, such as the division of domestic tasks ( 6 ).…”
Section: Discussionmentioning
confidence: 99%